2018
DOI: 10.1161/circimaging.117.006917
|View full text |Cite
|
Sign up to set email alerts
|

Disharmonious Patterns of Heterotaxy and Isomerism

Abstract: Atrial appendage morphology is difficult to assess and not always indicative of bronchopulmonary or abdominal situs. Discordance between bronchopulmonary branching, atrial appendage arrangement, and splenic status was identified in >20% patients with heterotaxy. Independent description of each organ system is required when arrangements are disharmonious among different organ systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…The reliable visualization of intracardiac and vascular anatomy, large field of view, and 3D imaging capabilities all make CMR well-suited for the diagnosis of complex cardiovascular anatomic arrangements, such as those seen in more severe forms of heterotaxy syndrome [ 79 , 80 ]. CMR is a non-invasive alternative to invasive cardiac catheterization and often provides a more comprehensive evaluation than echocardiography.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…The reliable visualization of intracardiac and vascular anatomy, large field of view, and 3D imaging capabilities all make CMR well-suited for the diagnosis of complex cardiovascular anatomic arrangements, such as those seen in more severe forms of heterotaxy syndrome [ 79 , 80 ]. CMR is a non-invasive alternative to invasive cardiac catheterization and often provides a more comprehensive evaluation than echocardiography.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…While the existing classification classifies situs ambiguous either with respect to the presence of the spleen or with respect to the atrium, these are in reality only associations [4]. Each case can have virtually any possible combination of abnormalities, making each case unique [5].…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, an exception to these general hallmarks is not infrequent as the features of classic isomerism were found breached in >20% of cases. [8]…”
Section: Discussionmentioning
confidence: 99%
“…Discordance between atrial appendage arrangement, splenic status, and bronchopulmonary branching was identified in a fair number of patients of heterotaxy postnatally. [8] Therefore, in vivo , atrial situs determination is mainly based on the general pattern of the associated cardiovascular and noncardiovascular findings than on the actual evaluation of the atrial morphology. [8] Interrupted IVC with azygous continuation into the SVC is a specific prenatal sonographic marker of LAI and was seen in 89.2%[5] to 100%[10] cases, while the juxtaposition of the aorta and the IVC is the main diagnostic feature of RAI in utero and was present in 81.5% fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation